WHY SHOULD GYNECOLOGIST ADDRESS ISSUES BREAST - Valdivia Ponce, Eduardo (2015)
"The integration and dependence of the breast in the female reproductive system is expressed. By reason of being a significant organ in the reproductive system and by reason of having a common pathology in relation to tax disendocrinias considered knowledge of gynecological field on the one hand, and on the other by the fact that the gynecological examination is incomplete if the breasts are not examined, the gynecologist is bound to know, diagnose, treat or at least steer you in the problems and pathology mom ".